2021
DOI: 10.3389/fpls.2021.646343
|View full text |Cite
|
Sign up to set email alerts
|

Translation Initiation Factor eIF4E Positively Modulates Conidiogenesis, Appressorium Formation, Host Invasion and Stress Homeostasis in the Filamentous Fungi Magnaporthe oryzae

Abstract: Translation initiation factor eIF4E generally mediates the recognition of the 5’cap structure of mRNA during the recruitment of the ribosomes to capped mRNA. Although the eIF4E has been shown to regulate stress response in Schizosaccharomyces pombe positively, there is no direct experimental evidence for the contributions of eIF4E to both physiological and pathogenic development of filamentous fungi. We generated Magnaporthe oryzae eIF4E (MoeIF4E3) gene deletion strains using homologous recombination strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…After observing the sporulation defect in MoSch9 deleted strains, the virulence efficacy of hyphae and asexual spores produced by ΔMoSch9 was investigated. As previously described [ 36 , 50 ], when 7 day old barley and 21 day old susceptible rice leaves were inoculated with mycelial plugs of wild type and mutant strains, MoSch9 deleted strains (ΔMosch9-33 and ΔMosch9-41) showed no lesion on intact and injured leaves of both barley and rice ( Figure 3 A,B). This indicates that deletion of MoSch9 completely abolished the hyphal mediated pathogenesis of M. oryzae .…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…After observing the sporulation defect in MoSch9 deleted strains, the virulence efficacy of hyphae and asexual spores produced by ΔMoSch9 was investigated. As previously described [ 36 , 50 ], when 7 day old barley and 21 day old susceptible rice leaves were inoculated with mycelial plugs of wild type and mutant strains, MoSch9 deleted strains (ΔMosch9-33 and ΔMosch9-41) showed no lesion on intact and injured leaves of both barley and rice ( Figure 3 A,B). This indicates that deletion of MoSch9 completely abolished the hyphal mediated pathogenesis of M. oryzae .…”
Section: Resultssupporting
confidence: 61%
“…Hyphal-mediated appressorium-like structures and appressorium of M. oryzae are the basic infectious structures responsible for the pathogen’s hyphal and spore-mediated blast infection, respectively, in the host plant [ 36 , 51 , 52 ]. Therefore, to identify the possible reasons that account for attenuation in the virulence of ΔMoSch9 strains, the formation of hyphal-mediated appressorium-like structures and their penetration capability was assessed by inoculating the mycelia of wild-type and ΔMoSch9 strains on barley leaves and hydrophobic coverslips.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As some proteins are constitutively synthesized by house-keeping genes at all developmental stages for the maintenance of primary cellular function there are some other group of proteins that are selectively expressed in response to the prevailing physiological and cellular need of the organism ( Zhang and Li, 2004 ), for this, we observed the expression pattern of MoCA1 at different developmental stages of M. oryzae and found that MoCA1 expression was specifically higher at the conidiophore stalk development and infectious stage ( Figures 2B , C ) which shows that MoCA1 is selectively expressed during M. oryzae life cycle especially during conidiation and pathogenic phase. Conidiation plays a key role not only in the survival and propagation of fungi under harsh environmental conditions but also facilitates the efficient disease prolongation ( Wyatt et al, 2013 ; Batool et al, 2021 ). Here we showed that the disruption of MoCA1 resulted in the impaired conidiophore formation, decreased conidiation and changes in appressorial development and melanization ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other putative candidate genes involved in the differentiation between the Gulf and the Atlantic support this scenario of ongoing adaption to environmental change. In Chr07, the transcript of the translation initiation factor eIF4E, known to regulate stress homeostasis and modulate host invasion (Batool et al, 2021), seems under selection. The detected Zinc finger protein 365 in Chr12 has been recently defined as a new maternal LPS-binding protein that defends zebrafish embryos against gram-negative bacterial infections (Du et al, 2018) and, in Chr15, the detected guanylate cyclase activator 1d has been shown to be involved into the regulation of the photoreceptor GC in the teleost's retina (Imanishi et al, 2004).…”
Section: Are Greenland Halibut Adapting To Climate Change?mentioning
confidence: 99%